Antimicrobial related problems in patients undergoing renal dialysis in a university hospital - Cristiane C. Santos; Elza A. Domingues (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Objective: To detect antimicrobial drug-related problems (DRP) in adult patients undergoing renal dialysis in a university hospital. Methods: This is an observational and retrospective study in which were included patients hospitalized in antimicrobial therapy and submitted to renal replacement therapy (RRT) from January to August 2017. The study variables were collected on the first day that antimicrobial was administraded and hemodialysis was done. The Dáder Methodology was used to detect and classify the DRP and probable negative outcomes associated with medications (NOMs). Results: 85 patients were included, 62.4% (n=53) male, mean age 61.2 ± 15.2 years. An average of 2.6 ± 1.6 different antimicrobials prescribed per patient was observed, being the main class carbapenems (13.7%) and the main reason for antimicrobial use was sepsis (34.1%). The main DRPs found were: prescription error (45.1%), Y incompatibility (14.0%) and inadequate dosage (12.1%), median 6.0 (4-11) DRP per patient, minimum:1 and maximum:32. Regarding NOMs, the most frequent were quantitative insecurity (50.6%), non-quantitative insecurity (19.9%) and quantitative ineffectiveness (19.0%). Conclusions: All patients undergoing dialysis and antimicrobial therapy included in this study had at least one problem related to antimicrobial drugs and, therefore, one probable NOM. It was verified the need of a multiprofessional team working on the detection and prevention of avoidable problems, through the implantation of computerized systems, continuing education program, protocols and routines, allied with an institutional antimicrobial stewardship program.